Pseudomonas aeruginosa ATCC 27853 as potential bio-control agent against the pathogen vibrio harveyi in prawn Penaeus monodon. - Pontila, Francis Luis (UPHSI, 2003)
In recent years, Vibrio harveyi has been infecting farmed prawns, Penaeus monodon. In 1996, Pseudomonas aeruginosa was found to inhibit local strains of Vibrio harveyi in vitro (Torrento et al, 1996.) To test its potential as bio-control agent, Pseudomonas aeruginosa must be challenged in prawn's rearing water. The study aims to test the potential of pseudomonas aeruginosa ATCC 27853 as bio-control agent against the pathogen, Vibrio harveyi based on the survival of Penaeus monodon and the concentration of Vibrio harveyi in the rearing water. Both treatments were infected with the pathogen Vibrio harveyi. Treatment A was inoculated with Pseudomonas aeruginosa ATCC 27853 and Treatment B was not. Survival of the prawns, Penaeus monodon and the concentration of Vibrio harveyi were determined at 0, 8, 16, 24, 72, and 144 hours after the inoculation of the bacteria. Salinity, temperature, and dissolved oxygen were monitored. Results showed that the concentration of Vibrio harveyi was lower in the treatment with Pseudomonas aeruginosa than in the other treatment. Survival of the prawns was higher in the treatment with Pseudomonas aeruginosa. Hence, we conclude that Pseudomonas aeruginosa strain ATCC 27853 can be potential biocontrol agent against the pathogen Vibrio harveyi.